The effect of bromocriptine on left ventricular functional recovery in peripartum cardiomyopathy: insights from the BRO‐HF retrospective cohort study. (22nd November 2018) - Tremblay‐Gravel, Maxime; Marquis‐Gravel, Guillaume; Avram, Robert; Desplantie, Olivier; Ducharme, Anique; Bibas, Lior; Pacheco, Christine; Couture, Etienne; Simard, François; Poulin, Anthony; Malhamé, Isabelle; Tran, Dan; et al.
Abstract: Aims: Bromocriptine is thought to facilitate left ventricular (LV) recovery in peripartum cardiomyopathy (PPCM) through inhibition of prolactin secretion. However, this potential therapeutic effect remains controversial and was incompletely studied in diverse populations. Methods and results: Consecutive women with new‐onset PPCM ( n  = 76) between 1994 and 2015 in Quebec, Canada, were classified according to treatment ( n  = 8, 11%) vs. no treatment ( n  = 68, 89%) with bromocriptine. We assessed LV functional recovery at mid‐term (6 months) and long‐term (last follow‐up) and compared outcomes among groups. Women treated with bromocriptine experienced better mid‐term left ventricular ejection fraction (LVEF) recovery from 23 ± 10% at baseline to 55 ± 12% at 6 months, compared with a change from 30 ± 12% at baseline to 45 ± 13% at 6 months in women treated with standard medical therapy ( P interaction < 0.01). At long‐term, a similar positive association was found with bromocriptine (9% greater LVEF variation, P interaction < 0.01). In linear regressions adjusted for obstetrical, clinical, echocardiographic, and pharmacological variables, treatment with bromocriptine was associated with a greater improvement in LVEF [β coefficient (standard error), 14.1 (4.4); P  = 0.03]. However, there was no significant association between bromocriptine use and the combined occurrence of all‐cause death and heart failure events (hazard ratio, 1.18; 95% confidence interval, 0.15 to 9.31), using univariable Cox regressions based over a cumulative follow‐up period of 285 patient‐years. Conclusions: In women newly diagnosed with PPCM, treatment with bromocriptine was independently associated with greater LV functional recovery.